Phytochemical analysis and assessment of antioxidant, antimicrobial, anti-inflammatory and cytotoxic properties of Tetraclinis articulata (Vahl) Masters leaves - Rached, Wahiba (2018)
Tetraclinis is an unexplored genus recognized for its great bioactive potential that could be explored as a medicinal herb. The aim of this study was to evaluate the antioxidant, antibacterial, anti-inflammatory and cytotoxic properties of the aqueous crude extract and subsequent organic fractions of the Algerian medicinal plant T. articulata. Moreover, polyphenols were also fully profiled by liquid chromatography with diode-array detection coupled to electrospray ionization in tandem with mass spectrometry (LC–DAD–ESI–MSn). The analysis of the obtained results show that B-type (epi)catechin dimer and catechin were the most abundant phenolic compounds present among the nine different flavonoids identified such as: ((epi)catechin, myricetin, quercetin and kaempferol glycoside derivatives). The concentration of phenolic compounds in the ethyl acetate fraction (93.1 mg/g extract) was higher than the one of the aqueous extract (21.2 mg/g extract) and butanol fraction (43.87 mg/g extract). Furthermore, the ethyl acetate fraction revealed the strongest bioactive properties, revealing the lowest EC50/GI50 values: anti-inflammatory (EC50 129.67 μg/mL), cytotoxicity against human tumor cell lines (GI50, 59–189 μg/mL), antibacterial (MIC, 0.625–10 mg/mL); and especially the antioxidant capacity (EC50 values lower than 12.7 μg/mL), even higher than the standard (Trolox). The results showed a great bioactive potential for this species, with a significant contribution of flavonoid compounds, which makes it an interesting matrix in the development of novel pharmaceutical formulations.